Sex and Sleep: Perceptions of Sex as a Sleep Promoting Behavior in the General Adult Population - Michele Lastella; Michele Lastella; Catherine O'Mullan; Jessica L. Paterson; Jessica L. Paterson; Amy C. Reynolds; Amy C. Reynolds (Frontiers Media S.A., 2019)
Objective: The main aim of this study was to explore the perceived relationship between sexual activities, sleep quality, and sleep latency in the general adult population and identify whether any gender differences exist.Participants/methods: We used a cross-sectional survey to examine the perceived relationship between sexual activity and subsequent sleep in the general adult population. Seven-hundred and seventy-eight participants (442 females, 336 males; mean age 34.5 ± 11.4 years) volunteered to complete an online anonymous survey at their convenience.Statistical Analyses: Chi square analyses were conducted to examine if there were any gender differences between sexual activities [i.e., masturbation (self-stimulation), sex with a partner without orgasm, and sex with a partner with orgasm] and self-reported sleep.Results: There were no gender differences in sleep (quality and onset) between males and females when reporting sex with a partner [χ(2)2 = 2.20, p = 0.332; χ(2)2=5.73, p = 0.057] or masturbation (self-stimulation) [χ(2)2 = 1.34, p = 0.513; χ(2)2 = 0.89, p = 0.640] involved an orgasm.Conclusions: Orgasms with a partner were associated with the perception of favorable sleep outcomes, however, orgasms achieved through masturbation (self-stimulation) were associated with the perception of better sleep quality and latency. These findings indicate that the public perceive sexual activity with orgasm precedes improved sleep outcomes. Promoting safe sexual activity before bed may offer a novel behavioral strategy for promoting sleep.